Phytobiotic-Prebiotic Feed Additive Containing a Combination of Carob Pulp, Chicory, and Fenugreek Improve Growth Performance, Carcass Traits, and Fecal Microbiota of Fattening Pigs - Ákos Juhász; Viviána Molnár-Nagy; Zsófia Bata; Ko-Hua Tso; Katalin Posta (Animals, 2023)
The purpose of this study was to determine the effectiveness of a phytobiotic-prebiotic feed additive (PPFA, which contains a combination of chicory and extracts of carob pulp and fenugreek) in the diets of fattening pigs on growth indicators, carcass characteristics, and fecal microbiota. A total of 329 crossbred pigs were randomly divided into two dietary treatments, including a basal diet without additives as the control group and a basal diet supplemented with 1 kg/T PPFA as the trial group. The PPFA supplementation led to a significant increase in the body weight gain and average daily gain of the trial group compared to those of the control group after 70 days of feeding. Through the S-EUROP evaluation system, we also found that the fattening pigs fed PPFA significantly improved their carcass indicators. Furthermore, it was shown that PPFA regulated porcine intestinal microbiota, including promoting the growth of the beneficial commensal bacteria (i.e., Bifidobacterium and Lactobacillus) while inhibiting some potential pathogen bacteria (i.e., Bacteroidaceae and Campylobacteraceae). Our work revealed that the phytobiotic-prebiotic feed additive containing carob pulp, chicory, and fenugreek positively influences the intestinal microbiota, growth performance, and carcass traits in fattening swine.